"As Good as Cash All the Time": Trapping Rabbits in South-Eastern Australia, 1870–1950. (1st November 2016) - Eather, Warwick; Cottle, Drew
Abstract : The rabbit industry was a boon for thousands of workers in the bush of south-eastern Australia between 1870 and 1950. While different forms of trapping required experience in specific methods to maximise income, little capital was required to get started. Contrary to their depiction as precarious proletarians constantly falling prey to the vicissitudes of climate, season and global markets, many rural workers were successful rabbiters enjoying high earnings and easier work. Rabbiting ended the continual search for low-paid, seasonal farm work and deprivation during winter months. Rabbiters and their families enjoyed relative financial security and severe economic downturns had little impact on the rabbit industry. The rabbit industry caused labour shortages across all types of rural work and reduced the ranks of the reserve army of labour in the bush. Different rural dwellers, from clergy to wheat lumpers, used these shortages or rabbiters' high earnings to secure higher pay. By making farming uneconomic in many areas, rabbit plagues made the impetus to trapping all the greater. These findings warrant a radical revision of the accepted wisdom about the nature of life and labour in rural Australia.